Rigorous analysis and pragmatic guidelines in estimating strain rate sensitivity using stress relaxation test. (May 2022) - Prasad, Kali; Balaji, Vikram; Krishnaswamy, Hariharan; Phani, P. Sudharshan; Carlone, Pierpaolo
Abstract: The exponent in power law relation between stress and strain rate during uniaxial deformation is known as strain rate sensitivity, m . The parameter provides valuable insights on the underlying rate dependent mechanical behavior. Although m can be estimated using macroscopic transient tests like strain rate jump test and stress relaxation test, the kinetics of the dislocation motion and its influence on the m is not well documented, resulting in ambiguity of the values estimated from different test procedures. In the present work, it is shown that the value estimated from stress relaxation test is not accurate owing to the transient nature of dislocation density during relaxation. A new methodology is demonstrated to accurately estimate m from stress relaxation test. The methodology is demonstrated using four different aging conditions of a commercially available AA 7075 alloy. A simplified closed form analytical equation is proposed for the ratio of strain rate sensitivities obtained from the traditional and new procedure. Highlights: Short coming of iso-structure assumption in determining strain rate sensitivity explained. A rigorous analytical procedure to estimate strain rate sensitivity from stress relaxation. simple analytical solution proposed to estimate the degree of accuracy of strain rate sensitivity. Accuracy of estimation can be uniquely correlated to dislocation annihilation during relaxation.